O posicionamento do tribunal de justiça do Estado do Maranhão sobre a dimensão jurídica das organizações sociais indígenas: (Des) entraves para a efetivação de um pluralismo jurídico - PACINI, Paulo Ferreira (2022)
The Federal Constitution of 1988 brought a new indigenist landmark to Brazil, breaking with centuries of assimilationist and integrationist tradition. However, its devices still largely lack the construction of meaning and or actual practice, given the use of vague legal concepts and abstract expressions that refer the interpreter to necessary aditional elements and knowledge zones that should not be necessarily considered extra-legal knowledge. The present research focuses on some of the aspects of this interpretative vacuum, more precisely the possibility of an effective legal pluralism in Brazil, implicit in the constitutional norm, but far from being materialized in practice. It aims to analyze how the Court of Justice of the State of Maranhão has positioned itself considering the face of the indisputable variety of indigenous rights, mainly the ones produced in their societies, using, for that purpose, the use of content analysis and other methodological procedures of judgments, and their respective cases, in which indigenous people appear as parties or in those in which they and their collectivities are affected by these decisions. For data analysis and to achieve conclusions, several analytical tools were used, highlighting the concepts of symbolic power and symbolic violence by Bordieu, as well as the concept of tutelary power, by Antônio Carlos de Sousa Lima, which allowed the identification of practices of invisibility of indigenous people in the organ studied, denial of rights expressed in national legislation, as well as serious ethical, political and epistemological obstacles that compromise the realization of an egalitarian legal pluralism in the country. The same analytical resources allowed the reflection on the limits and possibilities of this pluralism within the framework installed by the constitutional legislator, which go through a deep reflection on the dominant legal theories and their possible dialogue with interculturality, such as those proposed by Boaventura Santos, Segado and others authors. Keywords: